How do people with intellectual disabilities view abuse and abusers?. (December 2013) - Northway, Ruth; Melsome, Melissa; Flood, Samantha; Bennett, Davey; Howarth, Joyce; Thomas, Becki
People with intellectual disabilities have a higher risk of being abused than other people, but to date research has not explored their views regarding abuse. This article reports the findings relating to one question within a participatory research study concerning the abuse of people with intellectual disabilities. This question asked what people with intellectual disabilities' views are concerning abuse. Data were gathered via individual interviews ( n = 14) and focus groups (7 groups involving 47 people in total), which were then analysed via a process of sorting statements into themes followed by group discussion and analysis of these themes. Participants expressed a range of views regarding abuse, some of which revealed strong emotions: a number of participants indicated that abuse could make people feel as though their lives are not worth living. People with intellectual disabilities can discuss their feelings around abuse and recognise the impact this has on their lives. There is, however, a need for improved responses to disclosures of abuse and the provision of ongoing support to address psychological issues.